2005
DOI: 10.1021/ja051523f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Large Ring Metallacycle Intermediates in Polyethylene Chain Growth Using Homogeneous Chromium Catalysts

Abstract: Deuterio-ethylene labeling studies on two homogeneous chromium ethylene oligomerization catalysts show that chain propagation proceeds via metallacyclic intermediates; reactions performed in the presence of 1-nonene show no incorporation of the higher olefin, strongly implicating the involvement of large ring metallacycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 20 publications
7
122
0
4
Order By: Relevance
“…25 We were interested to find out whether this technique can also be applied to higher oligomers and polymers and we have therefore carried out Chromium catalysts 1 and 2 shown in Scheme 2 and related systems have been shown previously to be highly active for the oligomerization of ethylene. 18,[26][27][28] Preliminary cooligomerization experiments employing C 2 H 4 /C 2 D 4 (1:1) with these catalysts have shown that the oligomer fraction consists of even-numbered isotopologues only, which is consistent with a metallacyclic chain growth mechanism. 18 In addition, ethylene/1-nonene cooligomerization experiments with catalyst 1 have shown no incorporation of the higher 1-alkene.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…25 We were interested to find out whether this technique can also be applied to higher oligomers and polymers and we have therefore carried out Chromium catalysts 1 and 2 shown in Scheme 2 and related systems have been shown previously to be highly active for the oligomerization of ethylene. 18,[26][27][28] Preliminary cooligomerization experiments employing C 2 H 4 /C 2 D 4 (1:1) with these catalysts have shown that the oligomer fraction consists of even-numbered isotopologues only, which is consistent with a metallacyclic chain growth mechanism. 18 In addition, ethylene/1-nonene cooligomerization experiments with catalyst 1 have shown no incorporation of the higher 1-alkene.…”
Section: Introductionmentioning
confidence: 86%
“…18,30,31,33 The catalysts 1, 3 and 4 result in a Schultz-Flory distribution of linear α-olefins (LAO), while catalyst 2 gives a slightly different product distribution due to an additional, but minor, chain transfer to aluminum process. Chain transfer to aluminum is a common termination mechanism for catalyst 2 in the presence of MAO co-catalyst.…”
Section: H 4 Oligomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The total oligomer yield obtained at different gauge pressures from 1-4 bar follows a first order dependence on ethylene concentration (see Figure S2). The order in ethylene concentration for individual LAOs is conveniently determined from the slope in a ln(rate) versus ln[ethylene] plot, 44 whereby ethylene pressure is a reliable proxy for concentration in solution.…”
Section: Effect Of Pressurementioning
confidence: 98%
“…It is reported that chromium complexes ligated by NNN species such as bis(imino)pyridine, (2-pyridylmethyl)amines, β-diketimate and pyrrolide-imine ligands can polymerize or oligomerize ethylene with great activity [21,[23][24][25].…”
Section: Nnn Ligandsmentioning
confidence: 99%